HYPOTHESIS ON FORMATION OF THE MAGNETIC FIELD OF THE EARTH - J. Nurmatov; M. Barotov; Sh. S. Sharipov; K. J. Nurmatov (Galaxy International Interdisciplinary Research Journal, 2021)
This article defines developed hypothesis based on the dipolar theory on Earth magnetic field with the purpose of identifying and revealing importance of physical process in atmosphere and Earth magma, as well as importance of electrical macrodipolar in convergence of Earth into magnetic macro-dipolar has been explained. In order to describe meaning of hypothesis on new ideas related to Earth magnetism, provided are illustrated diagrams of physical process. It has been proven that in the course of research, developed is hypothesis on dipolar theory, its importance in geomagnetism and physical process has been explained. This hypothesis can be applied during study of magnetism theory and creating a new electrical dipolar theory on Earth geomagnetism, as well as in the course of physics education process.